Pengaruh Kenaikan Inflasi terhadap Kondisi Sosial Ekonomi Masyarakat Kota Kupang serta Implikasinya terhadap Kebijakan Ekonomi di Indonesia - Agustin, Sarlina; Clarissa, Maria; Nelo, Yolanda; Lawalu, Emiliana Matuti (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Inflation remains a critical macroeconomic issue with profound implications for developing regions, particularly Kupang City in East Nusa Tenggara, Indonesia. As a structurally vulnerable area with high dependency on external supply chains and limited local production capacity, inflation has deepened existing socio-economic challenges. This study aims to explore how rising inflation affects the social and economic conditions of communities in Kupang and to assess its implications for national economic policy formulation. Using a qualitative descriptive approach, the research involved semi-structured interviews with 25 informants—including low-income households, informal workers, micro-entrepreneurs, and local policymakers—alongside field observations and analysis of secondary data from official sources. Thematic analysis was applied to identify key patterns related to inflation’s local impact. The results reveal that inflation has led to declining purchasing power, reduced food quality and quantity, disrupted children’s education, and increased reliance on short-term aid. Micro and small enterprises face shrinking profit margins and operational closures due to rising input costs. Local authorities report limited capacity to respond effectively due to centralized economic governance. These findings affirm Keynes’ consumption theory and cost-push inflation dynamics, emphasizing that national inflation policy often overlooks regional disparities. The study recommends the development of context-sensitive policies such as improving local supply chains, empowering small enterprises, and expanding targeted welfare programs to build economic resilience in peripheral regions like Kupang.